2019
DOI: 10.1002/aocs.12315
|View full text |Cite
|
Sign up to set email alerts
|

Quality and Composition of Virgin Olive Oils from Indigenous and European Cultivars Grown in China

Abstract: The characteristics of eight varieties of virgin olive oil (Arbosana, Arbequina, Coratina, Cornicabra, Frantoio, Koroneiki, Picual, and Ezhi 8) obtained in two successive crops in the southwest of China (Xichang, Sichuan Province) were investigated. Significant differences (P < 0.05) were observed in physicochemical properties, fatty acid profile, minor component contents, and oxidative stability between different varieties of olive oils. The physicochemical properties of all samples met IOC standards for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 25 publications
2
16
3
Order By: Relevance
“…Nakbi et al 13 reported the OSI of olive oil from Tunisia 4.55-5.34 h , which was similar to that of Italy and Greece. Yu et al 14 compared eight varieties of VOO in the southwest of China; the OSI ranged from 4.15 to 24.42 h, and the maximum value was four times higher and the minimum value was lower than the results reported here. Therefore, the variety and the difference of origin has a considerable impact on the OSI of olive oil.…”
Section: Quality Parameterscontrasting
confidence: 69%
“…Nakbi et al 13 reported the OSI of olive oil from Tunisia 4.55-5.34 h , which was similar to that of Italy and Greece. Yu et al 14 compared eight varieties of VOO in the southwest of China; the OSI ranged from 4.15 to 24.42 h, and the maximum value was four times higher and the minimum value was lower than the results reported here. Therefore, the variety and the difference of origin has a considerable impact on the OSI of olive oil.…”
Section: Quality Parameterscontrasting
confidence: 69%
“…When SFF was compared with household oils, it is similar in fatty acid profile with major part as unsaturated fatty acids that are oleic and linoleic acids (Dorni et al., 2018). Moreover, SPF is comparable with olive oil and other oils when considering minor fatty acids (Dorni et al., 2018; Yu et al., 2020).…”
Section: Resultsmentioning
confidence: 91%
“…In general, the SFA content in our samples (22.6%) was found in higher concentrations than in Italian olive cultivars (13.1–17.6%) [ 36 ] and in Arbequina produced in different regions of Brazil and Spain [ 37 ]. Previous studies have demonstrated that the cultivar is an important factor that affects the composition of fatty acid in olive oils [ 38 ].…”
Section: Resultsmentioning
confidence: 99%